2008
DOI: 10.1021/jm701253t
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Protein Fluctuations at the Active-Site Gorge of Human Cholinesterases: Further Optimization of the Design Strategy to Develop Extremely Potent Inhibitors

Abstract: Protein conformational fluctuations are critical for biological functions, although the relationship between protein motion and function has yet to be fully explored. By a thorough bioinformatics analysis of cholinesterases (ChEs), we identified specific hot spots, responsible for protein fluctuations and functions, and those active-site residues that play a role in modulating the cooperative network among the key substructures. This drew the optimization of our design strategy to discover potent and reversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 85 publications
1
44
0
3
Order By: Relevance
“…10,15−18 Such inhibitors span the active-site gorge, and the nature of the linker affects the affinity for AChE and BuChE (dual or triple sites inhibitors 1a−c, Figure 1). 15 In order to develop innovative multifunctional pharmacological tools, based on our previous experience, we synthesized compounds 2a−c (Figure 1) by combining a bistacrine scaffold (for achieving hChEs inhibition) with a hydrophobic peptidomimetic sequence to interfere with the putative surface binding region of Aβ around W279, thus interfering with AChE-induced Aβ aggregation and Aβ selfassociation. 13 Molecular modeling studies ( Figure 2) and biological studies (Table 1 and Figure 3) confirmed our working hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,15−18 Such inhibitors span the active-site gorge, and the nature of the linker affects the affinity for AChE and BuChE (dual or triple sites inhibitors 1a−c, Figure 1). 15 In order to develop innovative multifunctional pharmacological tools, based on our previous experience, we synthesized compounds 2a−c (Figure 1) by combining a bistacrine scaffold (for achieving hChEs inhibition) with a hydrophobic peptidomimetic sequence to interfere with the putative surface binding region of Aβ around W279, thus interfering with AChE-induced Aβ aggregation and Aβ selfassociation. 13 Molecular modeling studies ( Figure 2) and biological studies (Table 1 and Figure 3) confirmed our working hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…13 Molecular modeling studies ( Figure 2) and biological studies (Table 1 and Figure 3) confirmed our working hypothesis. 15 The selection was based on its specific interaction with the three identified recognition sites of the hAChE gorge (observed by docking studies using hAChE), 15 which pushes the PAS oriented tacrine moiety to establish a triple π−π stacking with W286 and Y72 thus inducing a rotation of W286 (hAChE numbering). 15 Accordingly 2b,c demonstrated higher ability to inhibit hAChE Aβ aggregation while maintaining nM inhibition potency for hChEs.…”
Section: Introductionmentioning
confidence: 99%
“…It explains that the K i variations for both tacrine and bis(7)-tacrine were due to the reduction of the actual inhibitor concentration caused by the inhibitor binding to the inactive enzyme relative to the nominal inhibitor concentration. It also suggests that the reported K i variations for tacrine [15][16][17][18] were caused likely by the inhibitor binding to the inactive enzyme.…”
Section: Inactive Enzyme As Nontarget Binding Sitementioning
confidence: 98%
“…For example, the K i of tacrine was reported to be 20.2 ± 0.1 nM by one group and yet 340 ± 97 nM by another group for inhibiting Electrophorus electricus AChE (eeAChE) under the same Ellman assay conditions [15,16]. For another example, the K i of tacrine was reported to be 36 ± 1 nM by one group and later 137 nM by the same group for inhibiting recombinant human AChE under the same Ellman assay conditions [17,18]. These results raised concerns on the use of the experimentally determined K i as a measure of absolute binding affinity.…”
Section: Cc-by 40 International License Peer-reviewed) Is the Authormentioning
confidence: 99%
“…Mediated through the same mechanism, i.e., elevating the levels and duration of action of acetylcholine at synaptic clefts, these agents, however, only allow for the alleviation of the symptomatology in most patients and differ greatly in pharmacokinetic and pharmacodynamic profiles as well as result in adverse effects [7]. According to the crystallographic structural studies, AChE has a narrow 20 Å gorge with two binding sites: the catalytic active site (CAS) at the bottom of the structure and the peripheral anionic site (PAS) near the entrance of the gorge [8][9][10]. Consequently, inhibitors that bind to either one or two of the sites could inhibit the AChE.…”
Section: Introductionmentioning
confidence: 99%